Effectiveness of Fish Aggregating Devices in Freshwater Reservoir Fishery N. - N., Neethiselvan; N., Madhavan (Fishery Technology, 2025)
Two types of bottom set Fish Aggregating Devices (FADs), one of pyramidal shape and another of semi-prismatic shape were constructed using used tyres having a total outer surface area of 60 m2 . They were tested for their aggregating efficiency in an artificial freshwater reservoir stocked with freshwater carps such as catla (Catla catla), rohu (Labeo rohita), mrigal (Cirrhinus mrigala) and silver carp (Hypopthalmicthys molitrix). The gill net catch around FADs and in non-FAD sites showed significant difference. Pyramidal FAD of 1.6 m height with tyres arranged in vertical orientation attracted more of surface feeders such as catla and silver carp compared to semi-prismatic FAD of 1.3 m height with tyres arranged in horizontal pattern. The gill net catch around pyramidal FAD was significantly higher than that of semiprismatic FAD. The use of pyramidal FAD to improve catch per unit effort of gill netting in perennial reservoirs of the country, is suggested.